Pendidikan Hak Asasi Manusia dalam Kurikulum ‘Presisi’: Studi Sekolah Polisi Negara di Sumatera Utara - Rachman, Fazli; El Muhtaj, Majda; Perangin-angin, Reh Bungana Beru; Prayetno, Prayetno (Jurnal HAM, 2024)
This article focuses on the Indonesian Police (Polri) efforts in the realization of human rights-based policing, as well as its articulation in the forming education (pendidikan pembentukan/ DIKTUKBA) of Polri, specifically at the State Police School (Sekolah Polisi Negara/SPN) in North Sumatra, established in 1960-s and one of the oldest SPN in Indonesia. Since 2021, Polri has acknowledged and developed the ‘presisi’ curriculum to become a starting point for transformation agenda and, of course, to strive Polri’s obligation in the implementation of human rights values, principles and standards in the police functions. The research applied a qualitative approach with a descriptive design. Data collection was employed using documents, FGD, observations and literature relevant to police and human rights issues. Respondents were selected using a purposive sampling technique. Data validation was carried out by extending observations and triangulation and analyzed using the spiral technique. Human rights-based policing through the DIKTUKBA POLRI level at the SPN Poldasu brings the vision of ‘presisi’ police through the ‘presisi’ curriculum. The ‘presisi’ curriculum offers good ways to achieve the transformation of the Polri. However, the increasingly short training period for the DIKTUKBA POLRI represents a challenge to improve human rights-based policing. The challenges affirm the correlation between human rights and policing in a dynamic police workspace. In this context, the instructors’s capacity must continuously acquire knowledge and experience. Therefore, collaboration and innovation in using learning models and methods such as group learning, problem-solving, discussion, and active involvement of students can be continuously developed.